2017
DOI: 10.1038/s41598-017-09157-6
|View full text |Cite
|
Sign up to set email alerts
|

Phytotoxic dioxolanones are potential virulence factors in the infection process of Guignardia bidwellii

Abstract: Phytotoxic dioxolanones from Guignardia bidwellii can be described as potential virulence factors which cause the formation of lesions upon an infection by G. bidwellii. The toxin guignardic acid was found in planta of G. bidwellii-infected Vitis vinifera leaves, whereas no phytotoxic dioxolanones were detected in uninfected leaf material. Secondary metabolism analyses of further phytopathogenic fungi from the genus Guignardia led to the observation that all species investigated can produce the phytotoxins kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 25 publications
(37 reference statements)
0
13
0
Order By: Relevance
“…have been reported to have a similar metabolomic profile, including the dioxolanone phytotoxins which are regarded as potential virulence factors. However, one of these products, guignardic acid, has also been reported from P. capitalensis [80]. Biosynthetic abilities by endophytic strains of the latter species also refer to meroterpenes, such as compounds in the guignardone series [81][82][83][84] and the manginoids [85].…”
Section: Biotechnological Implicationsmentioning
confidence: 99%
“…have been reported to have a similar metabolomic profile, including the dioxolanone phytotoxins which are regarded as potential virulence factors. However, one of these products, guignardic acid, has also been reported from P. capitalensis [80]. Biosynthetic abilities by endophytic strains of the latter species also refer to meroterpenes, such as compounds in the guignardone series [81][82][83][84] and the manginoids [85].…”
Section: Biotechnological Implicationsmentioning
confidence: 99%
“…have been reported to have a similar metabolomic profile, including the dioxolanone phytotoxins which are regarded as potential virulence factors. However one of these products, guignardic acid, has been also reported from P. capitalensis [80]. Biosynthetic abilities by endophytic strains of the latter species also refer to meroterpenes, such as compounds in the guignardone series [81][82][83][84] and the manginoids [85].…”
Section: Biotechnological Implicationsmentioning
confidence: 99%
“…The investigation of dioxolanone as a virulence factor in four species of Phyllosticta were performed by Buckel et al [5]. The authors demonstrated that phenguignardic acid (1c) and guignardic acid are involved in the development of grape black rot, a serious disease in grapes.…”
Section: Introductionmentioning
confidence: 99%
“…S1). The chemical structure of the new metabolite (1a) was determined by cumulative 1D and 2D NMR spectroscopy, high resolution mass spectrometry (HRMS), chemical synthesis and by comparison with related structures [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation